Spinal Astrocyte Gap Junctions Contribute to Oxaliplatin-Induced Mechanical Hypersensitivity - Yoon, Seo-Yeon; Robinson, Caleb R.; Zhang, Haijun; Dougherty, Patrick M. (Churchill Livingstone, 2013)
Spinal glial cells contribute to the development of many types of inflammatory and neuropathic pain. Here the contribution of spinal astrocytes and astrocyte gap junctions to oxaliplatin-induced mechanical hypersensitivity was explored. The expression of glial fibrillary acidic protein (GFAP) in spinal dorsal horn was significantly increased at day 7 but recovered at day 14 after oxaliplatin treatment, suggesting a transient activation of spinal astrocytes by chemotherapy. Astrocyte-specific gap junction protein connexin 43 (Cx43) was significantly increased in dorsal horn at both day 7 and day 14 following chemotherapy, but neuronal (connexin 36 [Cx361]) and oligodendrocyte (connexin 32 [Cx32]) gap junction proteins did not show any change. Blockade of astrocyte gap junction with carbenoxolone (CBX) prevented oxaliplatin-induced mechanical hypersensitivity in a dose-dependent manner and the increase of spinal GFAP expression, but had no effect once the mechanical hypersensitivity induced by oxaliplatin had fully developed. These results suggest that oxaliplatin chemotherapy induces the activation of spinal astrocytes and this is accompanied by increased expression of astrocyte-astrocyte gap junction connections via Cx43. These alterations in spinal astrocytes appear to contribute to the induction but not the maintenance of oxaliplatin-induced mechanical hypersensitivity. Combined, these results suggest that targeting spinal astrocyte/astrocyte-specific gap junction could be a new therapeutic strategy to prevent oxaliplatin-induced neuropathy. Perspective: Spinal astrocytes but not micro glia were recently shown to be recruited in paditaxel-related chemoneuropathy. Here, spinal astrocyte gap junctions are shown to play an important role in the induction of oxaliplatin neuropathy. (C) 2013 by the American Pain Society